Rhizosphere and Straw Return Interactively Shape Rhizosphere Bacterial Community Composition and Nitrogen Cycling in Paddy Soil - Zhao, Ya-Hui; Wang, Ning; Yu, Meng-Kang; Yu, Jian-Guang; Xue, Li-Hong (Frontiers in Microbiology, 2022)
Currently, how rice roots interact with straw return in structuring rhizosphere communities and nitrogen (N) cycling functions is relatively unexplored. In this study, paddy soil was amended with wheat straw at 1 and 2% w/w and used for rice growth. The effects of the rhizosphere, straw, and their interaction on soil bacterial community composition and N-cycling gene abundances were assessed at the rice maturity stage. For the soil without straw addition, rice growth, i.e., the rhizosphere effect, significantly altered the bacterial community composition and abundances of N-cycling genes, such as archaeal and bacterial amoA (AOA and AOB), nirK, and nosZ. The comparison of bulk soils between control and straw treatments showed a shift in bacterial community composition and decreased abundance of AOA, AOB, nirS, and nosZ, which were attributed to sole straw effects. The comparison of rhizosphere soils between control and straw treatments showed an increase in the nifH gene and a decrease in the nirK gene, which were attributed to the interaction of straw and the rhizosphere. The number of differentially abundant genera in bulk soils between control and straw treatments was 13–23, similar to the number of 16–22 genera in rhizosphere soil between control and straw treatment. However, the number of genera affected by the rhizosphere effect was much lower in soil amended with straw (3–4) than in soil without straw addition (9). Results suggest possibly more pronounced impacts of straw amendments in shaping soil bacterial community composition.